Islam, Neo-Colonialism, And Factors Responsible For Its Roots In The Muslim World - Yahaya Sulaiman; Ruqayya Abubakar Kaura; Idris Salamatu Doma (Bulletin of Islamic Research, 2024)
This study examines the complex relationship between Islam and neo-colonialism, tracing the historical and contemporary factors that have contributed to the roots of neo-colonialism in the Muslim world. The research explores how colonial legacies, political and economic dependencies, and cultural imperialism have shaped the Muslim world's engagement with modernity and globalization. It analyzes the role of internal factors, such as authoritarianism, corruption, and sectarianism, in perpetuating neo-colonial dynamics. The study also investigates the impact of external factors, including Western foreign policy, globalization, and the War on Terror, on the Muslim world's political and economic landscape. The research employs a multidisciplinary approach, drawing on Islamic studies, postcolonial theory, and international relations to provide a nuanced understanding of the complex interplay between Islam and neo-colonialism. It argues that the roots of neo-colonialism in the Muslim world are multifaceted and deeply entrenched, requiring a comprehensive and contextualized approach to address. The study's findings highlight the need for Muslim societies to reclaim their agency, promote democratic governance, and foster economic self-sufficiency to counter the lingering effects of colonialism and neo-colonialism. Ultimately, this research aims to contribute to a deeper understanding of the complex dynamics shaping the Muslim world and inform strategies for promoting justice, equality, and self-determination in the region.